Pengujian Karakteristik Campuran AC-BC Yang Menggunakan Batu Gunung Baba, Tana Toraja - James Alfrian; Alpius; Louise Elizabeth Radjawane (Paulus Civil Engineering Journal, 2021)
This study was intended to determine the aggregate characteristics of the Batu Gunung Baba Tana Toraja Regency in the AC-BC mixture. The method is to conduct a series of characteristic tests for coarse, fine, and filler aggregates then design the composition of the AC-BC mixture and Marshall test to obtain the characteristics of the mixture and test the Marshall Immersion to obtain Marshall Stability The optimum residual bitumen content mixture. The results showed that the characteristics of the pavement material in the form of Mount Baba stone met the specifications as a road pavement coating material. Through the Marshall test, the characteristics of the AC-BC mixture were obtained with asphalt content of 5.0%, 5.50%, 6.0%, 6.50%, 7.0%. The results of Marshall Immersion test for AC-BC mixture with optimum asphalt content of 5.50%, obtained the remaining Marshall Stability of 96.47% fulfilling the 2018 Highways Specification, which is at least 90%.